Multicellular Bioprinting of Biomimetic Inks for Tendon‐to‐Bone Regeneration - Lin Du; Chen Qin; Hongjian Zhang; Fei Han; Jianmin Xue; Yufeng Wang; Jinfu Wu; Yin Xiao; Zhiguang Huan; Chengtie Wu (Advanced Science, 2023)
Abstract Tendon‐to‐bone interface has a hierarchical structure and gradient component that are conducive to distributing the stresses to achieve movement. Conventional biomaterials lack the capacity to induce synchronous repair of multiple tissues, resulting in the failure of the interface repair. Biomimetic strategies have attracted enormous attention in the field of complex structure regeneration because they can meet the different physiological requirements of multiple tissues. Herein, a biomimetic ink mimicking tendon/bone tissues is developed by combining tendon/bone‐related cells and Mo‐containing silicate (MS) bioceramics. Subsequently, biomimetic multicellular scaffolds are fabricated to achieve the simulation of the hierarchical structure and cellular composition of tendon‐to‐bone interfaces by the spatial distribution of the biomimetic inks via 3D bioprinting, which is of great significance for inducing the regeneration of complex structures in the interface region. In addition, attributed to the desirable ionic microenvironment created by MS bioceramics, the biomimetic scaffolds possess the dual function of inducing tendon/bone‐related cells tenogenic and osteogenic differentiation in vitro, and promote the integrated regeneration of tendon‐to‐bone interfaces in vivo. The study offers a feasible strategy to construct biomimetic multicellular scaffolds with bifunction for inducing multi‐lineage tissue regeneration, especially for regenerating soft‐to‐hard tissue interfaces.